Translocation of systemic fungicide thiophanate-methyl in soybean - and M. SRINIVAS PRASAD, B. SANTHA LAKSHMI*, J.P. GUPTA (Indian Phytopathology, 2002)
Thiophanate-methyl applied to seeds of soyabean cultivar Bragg was translocated upward in the soyabean plant. The organic solvents used for infusion of the fungicide differed in their ability to translocate the fungicide in the plant. In ten-day oldseedlings, ethanol followed by dichloromethane (DCM), trichloromethane (TCM) and acetone facilitated greater translocation of the fungicide to the cotyledons and roots, whereas carbon tetrachloride (CTC) and benzene translocated less fungicide than in the dry seed treatment. DCM, ethanol and TCM enabled greater translocation to the aerial parts. In twenty- and thirty-day-old plants, treatments with ethanol, DCM, TCM and acetone were superior to dry seed treatment, while CTC and benzene carried less fungicide. The fungicide could not be detected in 60-day-old plants and at maturity in any of the treatments. Thiophanate-methyl in ethanol and DCM proved to be the best in controlling charcoal rot (Macrophomina phaseolina) followed by TCM and acetone in comparison with the dry seed treatment alone, whereas CTC and benzene were ineffective.